COVID-19, an Emerging Coronavirus Infection: Current Scenario and Recent Developments – An Overview - Alfonso J. Rodríguez‐Morales; D. Katterine Bonilla‐Aldana; Ruchi Tiwari; Ranjit Sah; Ali A. Rabaan; Kuldeep Dhama (2020)
During December 2019, a novel coronavirus virus (2019-nCov) emerged in China, which posed an International Public Health Emergency in a couple of weeks, and very recently attained the position of a very high-risk category by World Health Organization (WHO). This virus was named the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) by the International Committee on Taxonomy of Viruses (ICTV), and the disease referred to as Coronavirus Disease-19 (COVID-19). Till March 8, 2020, the virus has claimed the lives of nearly 3,600 humans out a total of approximately 110,000 confirmed cases affected by this infection. The present editorial is a brief overview highlighting the most salient features and facts with regards to COVID-19, an emerging coronavirus infection, its causative virus (SARS-CoV-2), the current worldwide scenario, recent developments and currently ongoing progresses to contain and control this disease which have now spread to more than 100 countries across the globe. Of note, worldwide researchers and various health agencies are all together doing their best to halt the spread of this virus and avoid any possible pandemic situation to be faced, which otherwise would threaten the lives of millions of human beings.